PENENTUAN BOBOT BADAN SAPI PERANAKAN ONGOLE (PO) JANTAN BERDASARKAN PROFIL BODY CONDITION SCORE (BCS) DI KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG - Putra, Andhika; Rusdhi, Alfath; Gunawan, Fahri (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The study aims to estimatet the weight of male ongole (PO) crossbred cattle based on the BCS profile and the vital size of its body parts such as chest floor circumference, shoulders height and body length in the Hamparan Perak Subdistrict, Deli Serdang Regency. The method used in this study is purposive sampling method. The measurements were done by measuring the height of withers, the length of the body, the chest floor circumference and the weight of a cow. The finding using the Schrool formula, the Indonesian winter formula and the modified formula to estimate the body weight of male PO cattle have a fairly high difference in mean and standard deviation from the original body weight value. The difference between the Schrool formula and the original body weight is 99,86 with a standard deviation of 7,89. The difference using the Winter Indonesia formula on average is 84,33 with a standard deviation of 31,06 and the use of the modified formula results in an average difference of 16,79 with a standard deviation of 7,90. Thus, a modified formula is needed to estimate the body weight of male PO cows in Hamparan Perak Subdistrict, Deli Serdang Regency with results closer to the original body weight with an average of 2,14, and with a standard deviation of 10,49. The application of this modified formula is more efficient in estimating the body weight of male PO cattle in Hampran Perak Subdistrict, Deli Serdang Regency.